David the Invincible Commentary on Porphyry's Isagoge : Old Armenian text with the Greek original, and English translation, introduction and notes - David, the Invincible. (Philosophia Antiqua, 2014)
The Armenian version of David the Invincible's Commentary on Porphyry's Isagoge, although extremely literal, is shorter by a quarter than the Greek original and contains revised passages. The Greek text reproduces Busse's edition (1904) but sometimes preference is given to readings in the apparatus, corroborated by the Armenian version. The Armenian text is based on Arevšatyan's edition (1976), but seven more manuscripts have been consulted and some varia lectiones confirmed by the Greek original have been included in the text. The English translation is from the Armenian version. The passages of the Greek text without Armenian equivalent are translated into English as well. Also, the book contains Armenian marginal scholia.